Capital Budgeting Practice of Thai Firms - Champathed, Kereboon (Information Management and Business Review, 2015)
This paper examines the capital budgeting practice of Thai firms and the relationships between capital budgeting techniques and the firm size, length of operation and type of firms. The results indicated that most Thai firms used capital budgeting techniques for the analysis of investment projects (74.1%) and more than half (51.7%) of total corporate capital investment expenditures were screened by capital budgeting techniques. Discounted-cash-flow techniques were used by the majority of the firms with Internal Rate of Return (IRR) the most used evaluate techniques. Moreover, risk is quantified on individual project basis in assessing risk in investment decisions. Shortening the desired payback period was used most among the risk analysis techniques and the most likely scenario received most attention in the financial justification in relation to risk.